Peculiarities of training and advanced training of fingerprint experts - Petrova, Iryna; Kurdes, Oleg (Archives of Criminology and Forensic Sciences, 2021)
The Article purpose is identification of shortcomings in training, retraining and advanced training of fingerprint experts as well as outline of scientific basis for improving this area of activity. The analysis of domestic scientists’ developments has made it possible to establish that in Ukraine there is no single unified regulatory legal act governing training, retraining and advanced training of a forensic expert, regardless of his institutional subordination. It is proved that current regulatory legal framework for professional training of forensic experts, in particular fingerprint experts, of the system of the Ministry of Justice of Ukraine is at the stage of formation and development and requires further reformation. It is necessary to highlight the section: Procedure for specialists’ training and internship in the Regulations on the Central Expert Qualification Commission under the Ministry of Justice of Ukraine and Certification of Forensic Experts, and to develop a separate regulatory legal act regarding the procedure for advanced training on its basis. Particular attention is drawn to the absence of guidelines on the organization of the education process while forensic expert training, negatively affecting the process of learning during on-site training (in forensic science institutions). Expediency of the development of guidelines on forensic experts’ training for each individual expert specialization is established, which are suggested to be added as separate R&D topics to research work plan of the Ministry of Justice of Ukraine. It is indicated that a detailed study of the introduction of such a component as mentoring into the system of forensic experts’ training is essential. It is stressed that development of the regulatory legal framework for training forensic experts abroad in corresponding forensic science institutions, and the coordination of this area of activity by the Ministry will have a positive impact not only on the quality of training but also on the acquisition of world experience with the subsequent possibility of improving methods for conducting fingerprint analyses.